Mine Eyes Have Seen the Glory : a Journey into the Evangelical Subculture in America. - Balmer, Randall (Oxford University Press, USA, 2000)
Prologue 1. California Kickback 2. Dallas Orthodoxy 3. On Location 4. Phoenix Prophet 5. Adirondack Fundamentalism 6. Georgia Charismatics 7. Bible School 8. Campaign Journal 9. Mississippi Missions 10. Bible Bazaar 11. Episcopal Indians 12. Camp Meeting 13. City Crusade 14. Oregon Jeremiad Epilogue Index.